2014
DOI: 10.1371/journal.pone.0100398
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of a Non-β-Cell Source to β-Cell Mass during Pregnancy

Abstract: β-cell mass in the pancreas increases significantly during pregnancy as an adaptation to maternal insulin resistance. Lineage tracing studies in rodents have presented conflicting evidence on the role of cell duplication in the formation of new β-cells during gestation, while recent human data suggest that new islets are a major contributor to increased β-cell mass in pregnancy. Here, we aim to: 1) determine whether a non-β-cell source contributes to the appearance of new β-cells during pregnancy and 2) invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 43 publications
0
30
1
1
Order By: Relevance
“…Although most previous studies have demonstrated that beta cell replication is the predominant mechanism for post-natal beta cell expansion (28)(29)(30)(31)(32), specially during pregnancy (32,(34)(35)(36)(37)(38)(39)(40), involvement of beta cell neogenesis has also been reported (41,42). Thus, we (a) Beta cell mass quantification at G17 showed significant reduction in beta cell mass in L-NAME-treated pregnant mice.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Although most previous studies have demonstrated that beta cell replication is the predominant mechanism for post-natal beta cell expansion (28)(29)(30)(31)(32), specially during pregnancy (32,(34)(35)(36)(37)(38)(39)(40), involvement of beta cell neogenesis has also been reported (41,42). Thus, we (a) Beta cell mass quantification at G17 showed significant reduction in beta cell mass in L-NAME-treated pregnant mice.…”
Section: Discussionmentioning
confidence: 82%
“…Although most previous studies have demonstrated that beta cell replication is the predominant mechanism for post‐natal beta cell growth during pregnancy , there have also been reports suggesting occurrence of beta cell neogenesis . Thus, we examined possible changes in beta cell proliferation and beta cell neogenesis in the l‐ NAME‐treated mice.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In other situations of increased b-cell mass, including high-fat diet (17), drug-induced insulin resistance (18), or the physiological insulin resistance of pregnancy (19), b-cell proliferation, and not neogenesis, has been proposed as the main adaptive mechanism in rodents. However, recent studies have suggested that b-cell neogenesis also may contribute to the b-cell mass increase observed during pregnancy in mice (20) and humans (21).…”
mentioning
confidence: 99%
“…One example is pancreas growth during pregnancy in mice, where islet mass is increased and is a process recently shown to be dependent on serotonin levels [66]. To date, the source of these new beta cells during pregnancy is unclear [67]. However, the Kaestner group showed that islet expansion and beta cell hypertrophy occurred during pregnancy, and these processes induce both proliferative and survival pathways in response to increased metabolic demands [68].…”
Section: Adult Beta Cells From Endogenous Sourcesmentioning
confidence: 99%